ニホン ナンキョク エットウタイ ノ シュウダン セイカツ ト ソノ ヘンセン - 松田, 達郎; マツダ, タツロウ; Matsuda, Tatsuro (国立極地研究所, 1977)
P(論文) 1956年から1976年の間に日本南極観測隊は15の越冬隊を派遣し観測を行っている.これら越冬隊の集団生活について比較検討した.1)生活環境としての住居,電力供給,水供給の問題をとりあげて論じた.2)越冬隊の集団生活の中で,流行語,食物嗜好性,あだ名,食卓位置,映画上映等を通じ,集団としての特徴がみられる.3)越冬隊の運営について検討した.越冬隊が独自できめる隊内規則も年々変化している.会議開催数と越冬隊員数の間には相関がある.越冬隊内で発行された新聞は情報伝達に役立った. During the Japanese Antarctic Research Expedition between 1956 and 1976, 15 wintering parties were sent to Syowa Station. A comparative study on their life was made. 1) The changes of their living environments which included dwelling conditions, supply of electrical power and water supply were investigated. 2) There were some characteristics of a group in the wintering parties. These characteristics were shown by the words in vogue, tastes for food, nicknames, seating position at table, and screening. 3) The management of the wintering parties was studied. The rules for the management of wintering parties have changed gradually. There was a correlation between times of meetings, which were held during each wintering period, and the number of wintering persons. Newspapers which were published by some wintering parties were helpful with the information of them. departmental bulletin paper